Legal Utility of Consumer Protection Law For Bread Containing Hazardous Substances - Safirah, Asharin Sindy (Acten Journal Law Review, 2024)
Food is a basic need of society which is included in primary needs. Food needs are one of the human rights that must be fulfilled, both processed and unprocessed food. Processed food such as bread is also a public choice. The distribution of bread from producers as business actors to the hands of consumers certainly goes through a series of processes to detect the presence or absence of hazardous ingredients in the bread. The role of BPOM is very important in monitoring food circulating in the community. However, there are still many business actors who use hazardous materials to produce their products. The process of registering products with BPOM does not guarantee that business actors will continue to use ingredients that are safe for consumption. In practice, business actors use ingredients that are not in accordance with the composition at the time of product registration. Although BPOM has carried out its duties in monitoring the circulation of food in the community, the product has been circulating for a certain period of time which will certainly cause harm to consumers. This raises questions related to the expediency of the Consumer Protection Law as a consumer protector where the law should make people feel happiness and pleasure in consuming products, not sadness due to losses, as the theory of expediency put forward by Jeremy Bentham. Normative juridical research type as well as statutory and conceptual approaches will be used to find the benefits of consumer protection law for consumers of bread containing hazardous ingredients and ways to achieve these benefits. The benefits of consumer protection law will be achieved if supervision, enforcement of consumer protection law and BPSK empowerment are maximized in litigation dispute resolution to increase consumer satisfaction. Keywords : Legal Utility, Jeremy Bentham, Consumer